잠재감염에 의한 HBsAg 음성 B형 간염 급성 악화 1예 - 권영일; Young Il Kwon; 전대원; Dae Won Jun; 권오완; Oh Wan Kwon; 민지연; Ji Yeon Min; 정혜미; Hye Mi Jung; 두은영; Eun Young Doo; et al. (The Korean journal of medicine, 2012)
Many studies have recently reported reactivation in hepatitis B surface antigen (HBsAg)-negative subjects with the use of biologic agents such as rituximab. However, occult hepatitis B virus infection itself has little clinical impact. We experienced a case of acute exacerbation caused by occult hepatitis B infection without HBsAg seroconversion. No mutation was found on the major hydrophilic loop of the S protein. The patient recovered from acute exacerbation after antiviral therapy. In conclusion, acute exacerbation can be induced by occult hepatitis B virus infection itself without reactivation. In such a case, antiviral therapy should be considered. (Korean J Med 2012;83:619-623)